2017
DOI: 10.1007/s11011-017-9950-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apoptosis-regulatory genes in the hippocampus of rat neonates born to mothers with diabetes

Abstract: Diabetes during pregnancy impairs the development of the central nervous system (CNS) and causes cognitive and behavioral abnormalities in offspring. However, the exact mechanism by which the maternal diabetes affects the development of the brain remains to be elucidated. The aim of the present study was to investigate the effects of maternal diabetes in pregnancy on the expression of Bcl-2 and Bax genes and the numerical density of degenerating dark neurons (DNs) in the hippocampus of offspring at the first p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 126 publications
1
9
0
Order By: Relevance
“…They also suggested that hyperglycemia during pregnancy could cause a developmental change in the density of neuronal cells in the offspring's hippocampus [90]. In consist with this study, in another research has been reported that diabetes during pregnancy leads to up-regulate in Bax and down-regulated in Bcl-2 gene expression (apoptosis-regulatory genes) in the hippocampus of rat neonates born to mothers with diabetes [91].…”
Section: Effects Diabetes During Pregnancy On Hippocampussupporting
confidence: 71%
“…They also suggested that hyperglycemia during pregnancy could cause a developmental change in the density of neuronal cells in the offspring's hippocampus [90]. In consist with this study, in another research has been reported that diabetes during pregnancy leads to up-regulate in Bax and down-regulated in Bcl-2 gene expression (apoptosis-regulatory genes) in the hippocampus of rat neonates born to mothers with diabetes [91].…”
Section: Effects Diabetes During Pregnancy On Hippocampussupporting
confidence: 71%
“…The present study showed that hippocampi derived from the offspring of diabetic mothers are characterized by an increase in cell death and a higher susceptibility to damage caused by a second stressor, specifically bacterial endotoxin treatment. This effect may be explained by the hypothesis that hyperglycemia in utero may induce oxidative stress (the literature confirms that STZ leads to the overproduction of superoxides, peroxynitrates, hydroxyl radicals, and hydrogen peroxide, which are responsible for DNA damage and fragmentation, characterizing the genotoxic potential of STZ; Vikram et al 2007), apoptosis in target tissues and the alteration of the expression of genes involved in the proliferation and differentiation of brain cells, especially the downregulation of anti-apoptotic Bcl-2 and the upregulation of pro-apoptotic Bax (Hami et al 2013, 2015; Haghir et al 2017). Direct STZ cytotoxicity has also been demonstrated in hypothalamic and hippocampal neurons in STZ-treated animals and is evaluated by a decrease in the number of neurons and morphological changes in these animals (Bathina et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental investigations in animals indicated that uncontrolled diabetes mellitus was associated with morphological and functional alterations in the brain [ 10 12 ]. Hippocampus, a structure critical to cognitive processes, has been shown to undergo apoptotic cell death when subjected to hyperglycemic insult [ 13 15 ]. Diabetes during pregnancy strongly influences the regulation of both insulin-like growth factor-1 receptor (IGF-1R) and insulin receptor (InsR) in the rat hippocampus [ 13 ].…”
Section: Introductionmentioning
confidence: 99%